On unbounded solutions of the first order ordinary differential equations - Gudynas, Gintautas (Lietuvos matematikos rinkinys, 2001)
The article is concerned with Cauchy problem Gx(x, ξ) + H (x, G(x, ξ)) = 0,G(ξ, ξ)= + ∞Let H(x, y), Hy(x,y) ∈ C(R2) and H(x, y) ≻ a1 |y|1+a +a2 where a1, a2 ≻ 0. Then there exists the unique solution G(x, ξ) of Cauchy problem and it is general solution of this equation.